Level of Postnatal Checkup in Ethiopia – Implications for Child Health Services - Birhane, Binyam Minuye; Bayih, Wubet Alebachew; Mekonen, Demewoz Kefale; Chanie, Ermias Sisay; Demis, Solomon; Shimelis, Habtamu; Asferie, Worku Necho; Abebe, Eskeziaw; Addisu, Dagne; Nibret, Gedefaye; Endalamaw, Aklilu; Munye, Tigabu; et al. (Frontiers in Pediatrics, 2022)
Background High neonatal mortality rates continue to be a major public health issue in Ethiopia. Despite different maternal and neonatal care interventions, neonatal mortality in Ethiopia is at a steady state. This could be due to the low utilization of neonatal checkups. Thus, nationally assessing the level and predictors of postnatal checkups could provide important information for further improving neonatal healthcare services. Materials and Methods A secondary data analysis of the 2016 Ethiopia Demographic and Health Survey (EDHS) was performed on 7,586 women who had live births in the 2 years before the survey. All variables with a p-value of ≤0.25 in the bivariable analysis were entered into the final model for multivariable analysis, and the level of statistical significance was declared at a P-value of <0.05. Results According to the national survey, only 8.3% [95% CI: 8.19, 8.41] of neonates received postnatal checkups. About two-thirds of women, 62.8% had antenatal care visits, 67.9%, gave birth at home, and 95.7% were unaware of neonatal danger signs. Distance from health care institutions [AOR = 1.42; 95% CI: 1.06, 1.89], giving birth in a healthcare facility [AOR = 1.55; 95% CI: 1.12, 2.15], antenatal care visit [AOR = 3.0; 95% CI: 1.99, 4.53], and neonatal danger signs awareness [AOR = 3.06; 95% CI: 2.09, 4.5] were all associated with postnatal care visits. Conclusion The number of neonates who had a postnatal checkup was low. Increasing antenatal care visit utilization, improving institutional delivery, raising awareness about neonatal danger signs, increasing access to health care facilities, and implementing home-based neonatal care visits by healthcare providers could all help to improve postnatal checkups.